2022
DOI: 10.21203/rs.3.rs-1460002/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Measurement error risk for finger-cuff blood pressure after aortic valve replacement are aortic valve area index and heart rate; FloTrac vs ClearSight

Abstract: Purpose: The accuracy of ClearSightTM blood pressure measurements in patients with postaortic valve replacement may be inaccurate compared to intra-arterial pressure, the clinical risk of measurement discrepancy remains uncertain. This study aimed to determine the factors associated with errors in measurement. Methods: From October 2020 to November 2021, we collected 881 pairs of intra-arterial/ClearSight blood pressure measurements from 30 adults who underwent transcatheter aortic valve replacement. The agree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…In the operating room, some studies have shown reliable measures between the Nex n and invasive measurement with acceptable agreement for ABP ( There are only few studies that investigated 'clinical concordance' of non-invasive ABP measurement (Bugarini et al 2021;Kho et al 2022;Yahagi et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In the operating room, some studies have shown reliable measures between the Nex n and invasive measurement with acceptable agreement for ABP ( There are only few studies that investigated 'clinical concordance' of non-invasive ABP measurement (Bugarini et al 2021;Kho et al 2022;Yahagi et al 2022).…”
Section: Introductionmentioning
confidence: 99%